Modifications at K31 on the lateral surface of histone H4 contribute to genome structure and expression in apicomplexan parasites - Sindikubwabo, Fabien; Ding, Shuai; Hussain, Tahir; Ortet, Philippe; Barakat, Mohamed; Baumgarten, Sebastian; Cannella, Dominique; Palencia, Andrés; Bougdour, Alexandre; Belmudes, Lucid; Couté, Yohann; Tardieux, Isabelle; et al. (eLife, 2017)
An unusual genome architecture characterizes the two related human parasitic pathogens Plasmodium falciparum and Toxoplasma gondii. A major fraction of the bulk parasite genome is packaged as transcriptionally permissive euchromatin with few loci embedded in silenced heterochromatin. Primary chromatin shapers include histone modifications at the nucleosome lateral surface close to the DNA but their mode of action remains unclear. We now identify versatile modifications at Lys31 within the globular domain of histone H4 that crucially determine genome organization and expression in Apicomplexa parasites. H4K31 acetylation at the promoter correlates with, and perhaps directly regulates, gene expression in both parasites. By contrast, monomethylated H4K31 is enriched in the core body of T. gondii active genes but inversely correlates with transcription, whereas it is unexpectedly enriched at transcriptionally inactive pericentromeric heterochromatin in P. falciparum, a region devoid of the characteristic H3K9me3 histone mark and its downstream effector HP1.